(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2019)
The ethnographic film titled Lukomir, my home (2018) is a visual ethnography of the daily life of an elderly couple from Lukomir, the highest mountain village in the Federation of Bosnia and Herzegovina. It depicts transhumant sheepherders’ yearly migration cycle, during which they travel every winter with their flock of sheep from the Bjelašnica mountain ridge to the villages 30 km away, in the vicinity of Sarajevo. The film tracks the different spatial and material dimensions of their migration as well as their relationship to a life-style that is slowly disappearing. We see and sense the couple’s connection to the land, animals, and the overall changes to their social world. The film as a visual ethnography serves as a basis for the discussion of the anthropological understandings one can attain through audiovisual material in comparison to written research. Every research topic makes us expand upon our methodologies in various ways in order to explore how we need to look at a certain issue. The mutually constitutive exploration of one’s research topic and the employment of various visual media can reveal connections, sensorial dimensions and worldviews that otherwise perhaps would not be apparent. Through a reflexive analysis of the filming process as well as our field research, we can consider these important epistemological as well as methodological questions in the production of anthropological knowledge.